DALAIL KHAIRAT : MAKNA DAN SYAIR DALAM MENOLAK PAHAM WAHABI DI ACEH - Asmanidar Asmanidar (Prodi Studi Agama-Agama, 2022)
Dalail Khairat is one type of art that is very Islamic in Acehnese society, which consists of teachings and guidance that can set a person towards goodness and virtue or a medium of communication between a servant who prays and expresses his love for the Prophet. This research was conducted using a qualitative method that produces descriptive data with a phenomenological approach. The focus is on Dalail Khairat: Meaning and Poetry in Rejecting Wahhabism in Aceh. The method of data collection was done through observation, in-depth interviews, and documentation. The study of Dalail Khairat: Meaning and Poetry in Rejecting Wahhabism in Aceh shows that Dalail Khairat contains many meanings that can be learned from Dalail Khairat's poem about life in society, as well as can have a positive impact on things that exist in society. One of the aspects of the life of the Acehnese people is to create an atmosphere of intimacy, away from community members from its influence on current social phenomena, and Dalail Khairat can be preserved throughout the ages so that Acehnese regeneration knows about Dalail Khairat and can also know what is being played in the art of Dalail Khairat. In addition, Dalail Khairat also contains values such as family values, unity values, deliberation values, educational values (educative) and cultural values.